2015
DOI: 10.1186/s13012-015-0330-1
|View full text |Cite
|
Sign up to set email alerts
|

The transcatheter aortic valve implementation (TAVI)—a qualitative approach to the implementation and diffusion of a minimally invasive surgical procedure

Abstract: BackgroundThe transcatheter aortic valve implantation (TAVI), a minimally invasive surgical procedure to treat patients with severe symptomatic aortic stenosis, showed a rapid diffusion in Germany compared to the international level. The aim of this study is to identify and analyze factors affecting the implementation and diffusion of the procedure in hospitals using a qualitative application of the diffusion of innovations theory.MethodsWe conducted problem-centered interviews with cardiologists and cardiac s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 25 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…The first interpreta- Learning effect & diffusion of innovative medical devices Research Article tion is consistent with the results of a previous empirical study conducted in Italy on coronary stents [36]. The latter is line with a recent qualitative work, which demonstrated that the diffusion of TAVI in Germany has been influenced by multiple factors (e.g., perceived medical advantages of the new technology, social prestige of implanting centers and of clinicians, opinion leaders heading the departments, cooperation between cardiac surgeons and interventional cardiologists) that go beyond the level of reimbursement [37].…”
Section: Discussionsupporting
confidence: 80%
“…The first interpreta- Learning effect & diffusion of innovative medical devices Research Article tion is consistent with the results of a previous empirical study conducted in Italy on coronary stents [36]. The latter is line with a recent qualitative work, which demonstrated that the diffusion of TAVI in Germany has been influenced by multiple factors (e.g., perceived medical advantages of the new technology, social prestige of implanting centers and of clinicians, opinion leaders heading the departments, cooperation between cardiac surgeons and interventional cardiologists) that go beyond the level of reimbursement [37].…”
Section: Discussionsupporting
confidence: 80%
“…A total of 216 full texts articled were read. After the screening process, 33 studies, [ 27 59 ] reporting original primary data, met the eligibility criteria for this systematic review.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Patterns in financial reimbursement may affect the number of TAVR procedures that are currently performed, particularly in Europe. The current reimbursement system allows for liberal use of TAVR in Switzerland, Denmark, and Germany, whereas financial restrictions are quite marked in other European countries (eg, Spain, Portugal, United Kingdom) [47,48]. The number of TAVR might increase in these countries if the financial restrictions disappeared.…”
Section: Impact Of Intermediate-risk Trialsmentioning
confidence: 99%